Pembuatan Aneka Bakery Berbasis Umbi-Umbian Hasil Panen Jemaat GPdI Blessing Distrik Heram, Kota Jayapura - Herlina Menufandu; Nelly Lunga; Ign. Joko Suyono (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Tubers are one of the local foods besides rice and corn which have the potential as alternative food. Processing of tubers in Papua is generally still carried out simply and on small industry likes home industry. Various tuber are usually consumed by local people by boiled, fried, baked, and steamed. Many modern food are made from tuber flour to increase consumer interest. Generally, local people tuber crops are sold without going through modern processing. Low technological innovation and creation of local food causes the low consumer interest to consume various local food products. This activity was carried out with the aim of being GPdI, Blessing congregation, to increase the congregation insight so they interest to increase local food product by increase the nutritional value and selling value of the congregationâ€™s crops in modern packaging. Theoretical and practical methods are carried out with the intention of providing an explanation regarding the processing of tubers in to modern products. The practice was carried out so that the participants could directly make various bakeries made from tubers. During the activity, start to finish, participants were enthusiastic andÂ were able to produce various bakery produks such as bread, brudel, and brownis cake.Â Keyword: Tubers; Bakery; GPdI Blessing; Heram